PSYCHOLOGICAL INTERVENTIONS FOR SPORTS INJURY RECOVERY: A HYBRID SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Afif Khoirul Hidayat; Edi Purnomo; Zainul Aziz; Rahmawan Santoso; Nurlayli Hasanah; Carolus Wasa; Martha Betaubun (Journal of Physical Activity and Sports (JPAS), 2026)
Introduction: Psychological interventions have become integral to the rehabilitation process for athletes recovering from sports injuries. By addressing the psychological barriers that athletes face during rehabilitation, these strategies promote physical recovery and facilitate athletes' triumphant return to their sport with greater confidence and self-efficacy. Objective: This study explores the role of psychological interventions in sports injury recovery and highlights their integration into recovery protocols. Methodology: This study employs a hybrid approach combining a systematic literature review (SLR) and bibliometric analysis to explore psychological interventions for sports injury recovery. The SLR follows the PRISMA guidelines, synthesizing existing research published until January 26, 2026, while the bibliometric analysis, conducted using VOSviewer, provides a quantitative assessment of the research landscape. The study focuses on peer-reviewed English-language articles published on open-access platforms, mapping key themes, trends, and authors in the field. Results: The systematic review and bibliometric analysis identified six key psychological interventions for sports injury recovery: Deep Breathing, Goal Setting, Imagery, Relaxation, Self-Talk, and Social Support. These interventions are integral in reducing pain, anxiety, and negative emotional responses, enhancing athletes' adherence to rehabilitation programs. Conclusions: This study emphasizes the importance of integrating psychological interventions into the rehabilitation process to optimize both mental and physical recovery outcomes.